Activity-Dependent Synaptic Plasticity in Drosophila melanogaster - Bai, Yiming; Suzuki, Takashi (Frontiers in Physiology, 2020)
The Drosophila nervous system is a valuable model to examine the mechanisms of activity-dependent synaptic modification (plasticity) owing to its relatively simple organization and the availability of powerful genetic tools. The larval neuromuscular junction (NMJ) in particular is an accessible model for the study of synaptic development and plasticity. In addition to the NMJ, huge strides have also been made on understanding activity-dependent synaptic plasticity in the Drosophila olfactory and visual systems. In this review, we focus mainly on the underlying processes of activity-dependent synaptic plasticity at both presynaptic and postsynaptic terminals, and summarize current knowledge on activity-dependent synaptic plasticity in different parts of the Drosophila melanogaster nervous system (larval NMJ, olfactory system, larval visual system, and adult visual system). We also examine links between synaptic development and activity-dependent synaptic plasticity, and the relationships between morphological and physiological plasticity. We provide a point of view from which we discern that the underlying mechanism of activity-dependent plasticity may be common throughout the nervous systems in Drosophila melanogaster.